2014
DOI: 10.1063/1.4890729
|View full text |Cite
|
Sign up to set email alerts
|

On the use of explicitly correlated treatment methods for the generation of accurate polyatomic –He/H2 interaction potential energy surfaces: The case of C3–He complex and generalization

Abstract: Through the study of the C3(X1Σg (+)) (1)Σg (+)) + He((1)S) astrophysical relevant system using standard (CCSD(T)) and explicitly correlated (CCSD(T)-F12) coupled cluster approaches, we show that the CCSD(T)-F12/aug-cc-pVTZ level represents a good compromise between accuracy and low computational cost for the generation of multi-dimensional potential energy surfaces (PESs) over both intra- and inter-monomer degrees of freedom. Indeed, the CCSD(T)-F12/aug-cc-pVTZ 2D-PES for linear C3 and the CCSD(T)-F12/aug-cc-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…After considering the zero point vibrational energy correction (∼20 cm −1 ), we estimate a θ 2 angle of ∼20 • for the r 0 structure of CO 2 -N 2 , which is in excellent agreement with the empirical findings of Frohman et al 7 For 12 C 18 O 2 -14 N 2 , the θ 2 deviation from the C 2v equilibrium structure is estimated to be ∼6.8 • through the analysis of the infrared diode laser spectrum of this isotopologue. 8 The larger θ 2 and r 0 values for 16 O complex with respect to 18 O complex are in line with the smaller zero point energy (ZPE) for the heavier one and therefore on the location of the corresponding vibrationless level on the PES relative to the global minimum.…”
Section: Description Of the 4d-pessupporting
confidence: 61%
See 1 more Smart Citation
“…After considering the zero point vibrational energy correction (∼20 cm −1 ), we estimate a θ 2 angle of ∼20 • for the r 0 structure of CO 2 -N 2 , which is in excellent agreement with the empirical findings of Frohman et al 7 For 12 C 18 O 2 -14 N 2 , the θ 2 deviation from the C 2v equilibrium structure is estimated to be ∼6.8 • through the analysis of the infrared diode laser spectrum of this isotopologue. 8 The larger θ 2 and r 0 values for 16 O complex with respect to 18 O complex are in line with the smaller zero point energy (ZPE) for the heavier one and therefore on the location of the corresponding vibrationless level on the PES relative to the global minimum.…”
Section: Description Of the 4d-pessupporting
confidence: 61%
“…We established also that this level of theory is suited to generate accurate multidimensional PESs of weakly bound dimers with reduced computational cost. [12][13][14][15][16][17] At present, we take advantage of this technique to derive the 4D-PES of the CO 2 -N 2 complex along the intermonomer coordinates. Later on, we deduced an analytical representation of this 4D-PES.…”
Section: Introductionmentioning
confidence: 99%
“…Among the only two theoretical studies including the H 2 O vibration, the one of Faure et al 10,11 used the quasi-classical trajectory (QCT) method while the only quantum study was performed by some of us 12 for the collisions of H 2 O with H 2 using our recently developed Rigid-Bender Close-Coupling (RB-CC) method which includes explicitly the a) Electronic mail: thierry.stoecklin@u-bordeaux.fr b) Electronic mail: otoniel.denis@uautonoma.cl bending-rotation coupling for a triatomic molecules colliding with an atom. This work extended our previous studies dedicated to the collisions of linear triatomic molecules with atoms when including explicitly the bending-rotation coupling as for HCN 13,14 , DCN 15 and C 3 [16][17][18] colliding with He.…”
Section: Introductionsupporting
confidence: 52%
“…1 These so-called Swings emission bands 2 of C 3 were first reproduced in the laboratory by Herzberg 3 in 1942, although the final assignment of the rovibronic spectra was attributed to Douglas 4 and Gausset et al 5,6 Since then, the C 3 radical has been observed in a wide range of astrophysical sources, 7,8 including circumstellar shells of carbon stars, [9][10][11] interstellar molecular clouds, [12][13][14][15] and comets. 1,10 As the most abundant small pure carbon molecule in the interstellar medium, [16][17][18] C 3 along with its smaller congener C 2 are the central key to the formation of more complex carbon clusters, long-chain cyanopolyynes, carbon dust, and polycyclic aromatic hydrocarbons. 2,19,20 Mebel and Kaiser 21 provided alternative pathways, besides the C( 3 P j ) + C 2 H 2 (X 1 Σ + g ) reaction, 22 through which linear C 3 (  X 1 Σ + g ) would be formed in interstellar environments, i.e., in the reactions CH(X 2 Π Ω ) + C 2 (X 1 Σ + g ) and C( 3 P j ) + C 2 H(X 2 Σ + ), the latter being most relevant in interstellar space.…”
Section: Introductionmentioning
confidence: 99%
“…23 C 3 is also the predominant carbon cluster in equilibrium hot carbon vapor, 19,24 hydrocarbon flames, 2,19 and plasmas generated through energetic processing of carbon containing materials. 19,25,26 The relevance of the C 3 molecule in space 27 as well as in terrestrial sooting flames and combustion processes 2,19 has motivated many experimental [28][29][30] and theoretical 17,18,[31][32][33][34][35][36][37][38][39][40][41] ) electronic manifolds. 23,[38][39][40] It is worth pointing out that, from the theoretical perspective, much effort has been devoted to obtain local (near-equilibrium) ground state potential energy surfaces 42 (PESs) for C 3 aiming to explore its spectroscopy, notably the unusual large amplitude bending motion and related speculations concerning its quasi-linearity (for a comprehensive review, see Refs.…”
Section: Introductionmentioning
confidence: 99%